Nanomaterial-Based Repurposing of Macrophage Metabolism and Its Applications - Meng, Tingting; He, Danfeng; Han, Zhuolei; Shi, Rong; Wang, Yuhan; Ren, Bibo; Zhang, Cheng; Mao, Zhengwei; Luo, Gaoxing; Den, Jun (Nano-Micro Letters, 2024)
Macrophage immunotherapy represents an emerging therapeutic approach aimed at modulating the immune response to alleviate disease symptoms. Nanomaterials (NMs) have been engineered to monitor macrophage metabolism, enabling the evaluation of disease progression and the replication of intricate physiological signal patterns. They achieve this either directly or by delivering regulatory signals, thereby mapping phenotype to effector functions through metabolic repurposing to customize macrophage fate for therapy. However, a comprehensive summary regarding NM-mediated macrophage visualization and coordinated metabolic rewiring to maintain phenotypic equilibrium is currently lacking. This review aims to address this gap by outlining recent advancements in NM-based metabolic immunotherapy. We initially explore the relationship between metabolism, polarization, and disease, before delving into recent NM innovations that visualize macrophage activity to elucidate disease onset and fine-tune its fate through metabolic remodeling for macrophage-centered immunotherapy. Finally, we discuss the prospects and challenges of NM-mediated metabolic immunotherapy, aiming to accelerate clinical translation. We anticipate that this review will serve as a valuable reference for researchers seeking to leverage novel metabolic intervention-matched immunomodulators in macrophages or other fields of immune engineering. Highlights: 1 A large-scale metabolic adaptation in M1-polarized macrophages compared with M2 macrophages, along with multiple altered metabolite parameters that can serve as potential targets, have been discussed. 2 Nanomaterial-based repurposing of macrophage metabolism and its applications are systematically summarized and illustrated using representative examples. 3 Potential challenges, additional information about future research objectives, and priorities of nanomaterial-based macrophage immunotherapy are highlighted.